Maternal serum iron status, hepcidin and interleukin-6 levels in women with preeclampsia - Ahmed, Yasir I. B.; Yagoub, Hind S.; Hassan, Mohamed A.; Adam, I.; Hamdan, Hamdan Z. (Frontiers in Physiology, 2023)
Introduction: Preeclampsia can lead to a number of adverse maternal and perinatal effects. The association between iron status (serum iron, ferritin and total iron-binding capacity [TIBC]), unsaturated iron-binding capacity, hepcidin, interleukin-6 (IL-6) levels and preeclampsia is not fully understood. Objective: To assess the levels of iron status, hepcidin and interleukin-6 in women with preeclampsia compared with healthy pregnant women. Method: A case-control study (60 women were recruited in each group) was conducted at Saad Abuelela Maternity Hospital in Khartoum, Sudan. Sociodemographic and clinical data were gathered through a questionnaire. The levels of iron status, hepcidin and IL-6 were measured using applicable methods. Results. There was no significant difference in the median (interquartile range [IQR]) of age, parity or body mass index between the two groups. Moreover, the median (IQR) of the iron status, hepcidin and interleukin-6 did not differ between women with preeclampsia and healthy controls. There were no significant correlations between haemoglobin, hepcidin and IL-6. There were also no significant correlations between serum iron, serum ferritin, hepcidin and IL-6. However, there was a significant positive correlation between hepcidin and IL-6 (r = 0.393, p = 0.002). Conclusion: In this study, women with preeclampsia had levels of iron status, hepcidin and IL-6 similar to those observed in healthy pregnant women. There was no significant correlation between iron status, hepcidin and IL-6.